Roles of charged particles and reactive species on cell membrane permeabilization induced by atmospheric-pressure plasma irradiation. (22nd June 2016) - Sasaki, Shota; Kanzaki, Makoto; Hokari, Yutaro; Tominami, Kanako; Mokudai, Takayuki; Kanetaka, Hiroyasu; Kaneko, Toshiro
Abstract: As factors that influence cell membrane permeabilization during direct and indirect atmospheric-pressure plasma irradiation, charged particle influx, superoxide anion radicals (O2 − ∙), and hydrogen peroxide (H2 O2 ) in plasma-irradiated solution were evaluated. These are the three strong candidate factors and might multiply contribute to cell membrane permeabilization. In particular, a shorter plasma diffusion distance leads to the enhancement of the direct effects such as charged particle influx and further increase cell membrane permeability. In addition, O2 − ∙ dissipates over time (a life span of the order of minutes) in plasma-irradiated water, and the deactivation of a plasma-irradiated solution in term of cell membrane permeabilization occurs in a life span of the same order. These results could promote the understanding of the mechanism of plasma-induced cell membrane permeabilization.